Detection of Pantograph Collector Strips Using Correlation Method - Karaduman, Gulsah; Karakose, Mehmet; Aydin, Ilhan; Akin, Erhan (Ieee, 2019)
Pantographs are the equipment that transports the necessary energy from the catenary line to the locomotive for the movement of electric trains on railways. The pantographs provide this transmission with contact of the collector strips to the catenary. The collector strips, which are in continuous contact with the catenary system, may wear over time. This wear may cause faults or even breakage of the pantograph and catenary system. This threatens the safety of transportation. Therefore, continuous monitoring of the pantograph-catenary system is highly necessary. In this study, the detection of the pantograph's collector strips by correlation method is explained. This method does not require edge detection or filtering algorithms which are used as pre-processing by general computer vision techniques. Three different pantograph videos were used in this study. Successful results have been obtained with regard to the detection of the pantograph.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Catenary; correlation; computer vision; railway